Sustainability-Oriented Marketing dan Implikasinya pada Pemasaran Produk Ramah Lingkungan: Sebuah Literature Review - Destha Haddy Permana; Derri Kusuma; Yafi Sabila Rosyad; Desmon (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2026)
Climate change, environmental degradation, and the growing global awareness of sustainability have positioned sustainability-oriented marketing as a crucial element of contemporary business strategy. This article aims to systematically synthesize and analyze the academic literature on eco-friendly product marketing strategies by identifying key concepts, theoretical foundations, empirical findings, and existing research gaps. A systematic literature review (SLR) was conducted following PRISMA guidelines, analyzing 31 peer-reviewed articles published between 2015 and 2025 and retrieved from Scopus and Google Scholar databases. The findings reveal that existing studies predominantly focus on purchase intention rather than actual consumer behavior, lack longitudinal research designs, and provide limited integration of digital technologies, artificial intelligence, ethics, and greenwashing within a unified analytical framework. Furthermore, empirical evidence from SMEs and developing countries remains scarce. This study contributes to the marketing literature by offering a comprehensive thematic mapping of sustainability-oriented marketing research and proposing future research directions that emphasize integrative models, contextual relevance, and behavioral outcomes to advance sustainable consumption and business practices.